The Probiotic Lactobacillus paracasei Ameliorates Diarrhea Cause by Escherichia coli O8via Gut Microbiota Modulation1 - Ren, Shunan; Wang, Chunjie; Chen, Aorigele; Lv, Wenting; Gao, Ruijuan (Frontiers in Nutrition, 2022)
Background: Koumiss is a fermented horse milk food containing abundant probiotics. Lactobacillus paracasei is a bacterial strain isolated from koumiss that helps regulate the intestinal microflora. One of the major cause of diarrhea is a imbalance of the intestinal flora. The aim of this study was to investigate whether Lactobacillus paracasei can ameliorate E. coli-induced diarrhea and modulate the gut microflora. Methods: Mouse models of diarrhea were established via intragastric E. coli O8 administration. We then attempted to prevent or treat diarrhea in the mice via intragastric administration of a 3 × 108 CFU/mL L. paracasei cell suspension. The severity of diarrhea was evaluated based on the body weight, diarrhea rate and index, fecal diameter, ileum injury, hematoxylin-eosin (H&E) staining, and diamine oxidase (DAO) and zonulin expression. Expression of the tight junction (TJ) proteins claudin-1, occludin, and zona occludens (ZO-)1 were detected by immunohistochemistry (IHC). Gastrointestinal mRNA expression levels of interleukin (IL)-6, IL-1β, and tumor necrosis factor (TNF)-α were detected by real-time polymerase chain reaction (RT-PCR). The microbial composition was analyzed by 16s rRNA sequencing. Results: The L. paracasei demonstrated excellent therapeutic efficacy against diarrhea. It elevated the TJ protein levels and downregulated proinflammatory cytokines IL-6, IL-1β, TNF-α, and p65, myosin light chain 2 (MLC2), myosin light chain kinase (MLCK). Moreover L. paracasei increased those bacteria, which can product short-chain fatty acid (SCFA) such Alistipes, Odoribacter, Roseburia, and Oscillibacter. Conclusion: L. paracasei ameliorated diarrhea by inhibiting activation of the nuclear factor kappa B (NF-κB)-MLCK pathway and increasing the abundance of gut microflora that produce SCFA.